Interaksi Sosial Mahasiswa Kelompok 52 KKN-TT dalam Upaya Pemberdayaan Potensi Masyarakat di Desa Cibeber I, Kecamatan Leuwiliang, Kabupaten Bogor - Arief Goeritno; Prawitra Azhari Robby; Pratiwi Pratiwi; Widdy Tanzila (Universitas Mathla'ul Anwar Banten, 2019)
SOCIAL INTERACTION OF THE STUDENTS ON GROUP 52 OF KKN-TT FOR EMPOWERMENT EFFORTS OF THE COMMUNITY POTENCY IN CIBEBER I VILLAGE, LEUWILIANG, BOGOR.Group 52 of KKN-TT was one of the groups in the community service program held by the Bogor Ibn Khadun University in the City of Bogor. The Group 52 of KKN-TT activity was devoted to communities in Cibeber I Village, Leuwiliang, Bogor with three main programs and three supporting programs. The main programs cover the fields of formal and non-formal teaching, health and environment, and religion, while supporting programs include the economic field, the use of information technology, and relations in society. The six fields in the work program consist of fifteen types of planned and scheduled activities. Fifteen types of activities are a form of social interaction between students on Group 52 of KKN-TT and community in a potency of empower of the community. The achievement of all activities ranges from 80% to 100% with a number of impacts on the community, in the form of long-term benefits.